Economic Impacts of China's Accession to the World Trade Organization - Ianchovichina, Elena; Martin, William (World Bank, Washington, DC, 2014)
Ianchovichina and Martin present estimates of the impact of accession by China and Chinese Taipei to the World Trade Organization. China is estimated to be the biggest beneficiary, followed by Chinese Taipei and their major trading partners. Accession will boost the labor-intensive manufacturing sectors in China, especially the textiles and apparel sector that will benefit directly from the removal of quotas on textiles and apparel exports to North America and Western Europe. Consequently, developing economies competing with China in third markets may suffer relatively small losses. China has already benefited from the reforms undertaken between 1995 and 2001 (US$31 billion) and trade reforms after accession will lead to additional gains of around $US10 billion. Accession will have important distributional consequences for China, with wages of skilled workers and unskilled nonfarm workers rising in real terms and relative to farm incomes. Reduction in agricultural protection may hurt some farmers. Possible policy changes considered to offset these impacts include reductions in barriers to labor mobility and improvements in rural education. The authors estimate that the removal of the hukou system would raise farm wages and allow 28 million workers to migrate to nonfarm jobs. If, in addition, there is an increase in education spending that results in a percentage point increase in the annual skilled labor growth rate, approximately 32 million farm workers would leave their job for jobs in the nonfarm sectors. These policies would not only facilitate the evolution of China's economy toward high-technology manufacturing and services, they have the potential to much more than offset any negative impacts of accession on rural wages and rural incomes generally.